The historical evolution of the Greek retail trade: A first overview of its organisational-functional and spatial restructuring - Manolis Manioudis; Giorgos Meramveliotakis (Journal of Innovation and Entrepreneurship, 2023)
The history of retailing has become an area of growing scholarly interest over the last few decades, with publications mainly concerning the national historiography of retail and wholesaling. On the other hand, although the retail sector is considered to be one of the most historically significant sectors of the Greek economy, the economic history of the Greek retail industry remains a notoriously underdeveloped area of inquiry and, as such, is on the margins of economic and social studies in Greek historiography. In this paper, we, attempt to provide a first concise (and certainly not exhaustive) analysis of the historical development of the Greek retail sector from the nineteenth century to the present (in circa) day. Specifically, we aim to analyse the evolution of the Greek retail trade to assess the spatial and social impacts associated with establishing and operating "new forms" of commerce. The focus is on the sectoral and organisational restructuring of the retail trade with the changes in the standards of the spatial location, which relate to the establishment and operation of retail businesses. Students and scholars of the history of retailing would benefit from this worthwhile exercise which for the first time provides a first overview of the historical development of the Greek retail sector.
Keywords: 650; Consumption; Department stores; Greek retailing; History of retailing; Organisational structure; Small shops; Spatial restructure